2001
DOI: 10.1046/j.1365-2672.2001.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of bacteria from fabrics to hands and other fabrics: development and application of a quantitative method usingStaphylococcus aureusas a model

Abstract: Aims: To develop and apply a quantitative protocol for assessing the transfer of bacteria from bleached and undyed fabrics of 100% cotton and 50% cotton + 50% polyester (poly cotton) to ®ngerpads or other pieces of fabric. Methods and Results: Test pieces of the fabrics were mounted on custom-made stainless steel carriers to give a surface area of 1 cm in diameter, and each piece seeded with about 10 5 cfu of Staphylococcus aureus from an overnight broth culture; the inoculum contained 5% fetal bovine serum as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 19 publications
1
122
2
5
Order By: Relevance
“…Since the preparation of antimicrobial textiles is regarded as a promising means to minimize hospital-acquired infections due to a reduction of bacterial spread [18,19], for our current study we chose textile fabrics as model surfaces: cotton as cellulose based surface and polyester-poly(ethylene terephthalate) (PET).The advantage of the approach reported here is that: (i) antimicrobial polymers used in the current work were prepared using simple one pot reactions in water without using any catalyst, starting from cheap and commercially available starting materials; (ii) the textiles were coated with the polymers following a padding procedure used in industry; (iii) the presence of 0.5 %owf-1 %owf (on weight-of-fabric (owf)) polymers on the textile surface makes the whole textile very efficient (99.99% bacterial growth inhibition before and after repeated washings). …”
Section: Introductionmentioning
confidence: 99%
“…Since the preparation of antimicrobial textiles is regarded as a promising means to minimize hospital-acquired infections due to a reduction of bacterial spread [18,19], for our current study we chose textile fabrics as model surfaces: cotton as cellulose based surface and polyester-poly(ethylene terephthalate) (PET).The advantage of the approach reported here is that: (i) antimicrobial polymers used in the current work were prepared using simple one pot reactions in water without using any catalyst, starting from cheap and commercially available starting materials; (ii) the textiles were coated with the polymers following a padding procedure used in industry; (iii) the presence of 0.5 %owf-1 %owf (on weight-of-fabric (owf)) polymers on the textile surface makes the whole textile very efficient (99.99% bacterial growth inhibition before and after repeated washings). …”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is the major causative agent of mastitis in cows (Rabello et al 2007) and have been detected in milk and milk products (Morandi et al 2009;Ertas et al 2010). Skin microflora on workers' hands can be a secondary bacteria food contaminant (Sattar et al 2001). During the production, storage, and distribution of milk and dairy products, bacteria can proliferate and subsequently produce staphylococcal enterotoxins (SEs).…”
mentioning
confidence: 99%
“…However, even with real hands, varying transfer rates will be yielded in practice. It was previously shown that the transmission of micro-organisms is highly dependent on the degree of moisture on the hands as well as of recipient surfaces, with the transfer of bacteria always being significantly greater between moistened hands and objects than for dry ones (Marples and Towers 1979;Sattar et al 2001).…”
Section: Discussionmentioning
confidence: 99%